2020
DOI: 10.1111/rda.13677
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Mullerian hormone and its relationship to ovulation response and fertility in timed AI Bos indicus heifers

Abstract: This study evaluated the association between plasma anti‐Mullerian hormone (AMH) concentration and fertility in Nelore (Bos indicus) heifers submitted to timed artificial insemination (TAI). At the onset of the synchronization protocol, heifers (n = 289) received a subcutaneous P4 ear implant (3 mg) and 2 mg of oestradiol benzoate. Eight days later, the P4 implant was removed and 0.5 mg of oestradiol cypionate, prostaglandin (0.265 mg, i.m.) and equine chorionic gonadotropin (300 UI, i.m.) was administered, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
2
0
1
Order By: Relevance
“…The circulating concentrations of AMH are highly variable among mammalian species. In the current study, the AMH mean agreed with Zebu cattle reports, which ranged from 1.20 to 1.60 ng/mL [21,24,48]. These values were higher when compared with those reported for Taurine breeds (0.78 ng/mL [52]).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The circulating concentrations of AMH are highly variable among mammalian species. In the current study, the AMH mean agreed with Zebu cattle reports, which ranged from 1.20 to 1.60 ng/mL [21,24,48]. These values were higher when compared with those reported for Taurine breeds (0.78 ng/mL [52]).…”
Section: Discussionsupporting
confidence: 88%
“…In vitro fertilization and cattle embryo production are common practices in beef cattle production systems, especially in Zebu breeds [ 13 , 14 , 15 ]. The measurement of AMH concentration and its association with reproductive and fertility traits were widely studied in livestock, including cattle [ 16 , 17 , 18 , 19 , 20 , 21 ]. These studies indicated that circulating AMH levels are a useful indicator of fertility and reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha propuesto también la AMH como un marcador para predecir el desempeño de la PEIV en Bos taurus (25,26) y Bos indicus, como la raza Nelore (27,28,29). De esta forma, la AMH como marcador endocrino de la PFA, puede ser útil para seleccionar hembras donantes con alto potencial reproductivo y garantizar una mayor eficiencia en la producción de embriones (22,30).…”
Section: Introductionunclassified
“…After all, the carryover of chemicals into food products, such as sheep milk and meat, is increasing concerns of public health. Also, because one of the reproductive indicators we evaluated is serum AMH concentration and, synchronisation programs might reverse the possible association between AMH and patterns of follicle growth (Batista et al, 2020;Ribeiro et al, 2014). Moreover, Morotti et al, (2017) found that AMH concentrations, according to progesterone above or below one ng/mL were not different.…”
Section: Absence Of Oestrus Synchronisation In the Ewe Lambsmentioning
confidence: 96%